Is it safe the empirical distal femoral resection angle of 5° to 6° of valgus in the Brazilian geriatric population?() - Rezende, Fernando Cury (Rev Bras Ortop, 2013)
OBJECTIVE: The purpose of this study is to determine if there is a safe distal femoral resection angle to restore the normal axial alignment of the limb in total knee arthroplasty (TKA) in the Brazilian geriatric population with knee arthrosis. METHOD: This study analyzed 99 pre-operative hip-knee-ankle radiographs of osteoarthritic knees of 66 patients (54 women, 12 men) with knee osteoarthritis. The distal femoral cut angle was determined based on the femoral mechanical-anatomical angle (FMA). Mean, median and standard deviation measurements of the distal femoral cut angle were calculated, differentiated by gender and side. The mean result of the distal femoral resection angle was compared to 5.7°, the mean average angle of previous and similar study based on European population of patients with knee arthrosis. RESULTS: The mean average of the distal femoral resection angle of the study was 6.05 (range 3–9°). The distribution of this angle between genders showed a slight superior average of the male population (6.17°) compared to the female (6.02°), but with no statistically significant difference (p = 0.726). There was no statistically significant difference (p = 0.052) between the mean average of this study (6.05°) compared to the mean average of the literature (5.7°). However, considering 3° as the limit of acceptable error in the coronal plane, this empirical femoral resection angle would not be appropriated for 19.7% of the population. CONCLUSION: The distal femoral resection angle of 5–6° is not completely safe for the Brazilian geriatric population.